Curved Perylene Diimides Fused with Seven‐Membered Rings. Issue 6 (9th February 2021) - Fujimoto, Keisuke; Izawa, Seiichiro; Takahashi, Ayumu; Inuzuka, Toshiyasu; Sanada, Kazutaka; Sakamoto, Masami; Nakayama, Yasuo; Hiramoto, Masahiro; Takahashi, Masaki
Abstract: Curved perylene diimides fused with seven‐membered rings have been synthesized using a regioselective bay‐functionalization method and Pd‐catalyzed intramolecular C−H/C−Br coupling reaction. X‐Ray analysis and temperature‐dependent NMR spectroscopy revealed the curved molecular structure with a certain degree of conformational flexibility. The curved and expanded π‐conjugation altered the electronic properties while retaining the intrinsic properties of the parent perylene diimide. Despite the absence of solubilizing N ‐substituents, the curved perylene diimides showed sufficient solubility for application in solution‐processed organic photovoltaic devices. The devices showed superior performance with a power conversion efficiency of up to 2.76% due to suppressed charge recombination. Our detailed investigations suggest that the introduction of a curved structure enables the removal of the bulky N ‐substituents, which is an effective way to achieve a thin‐film morphology suitable for photoelectric conversion. Abstract : Curved perylene diimides fused with seven‐membered rings have been synthesized. Despite the absence of solubilizing N ‐substituents, the curved perylene diimides showed sufficient solubility due to their curved and flexible conformation. The introduction of a curved structure was proven to be a new design strategy for the development of future non‐fullerene acceptor materials for solution‐processed bulk heterojunction organic photovoltaics.